Patterns of psychiatry morbidity in referred patients attending psychiatry out patient department in a tertiary centre - Malla, Deep Prakash; Basnet, Rachana Sharma; Pokharel, Aakriti Malla (Journal of Kathmandu Medical College, 2017)
Background: Consultation-liaison psychiatry is an important part of psychiatry dealing with cases having co morbid general medical conditions. Psychiatrists need to be involved in evaluation of patients referred from other specialties.Objectives: To assess the patterns of psychiatry morbidity in referred patients attending psychiatry out patient department of Kathmandu Medical College.Methods: A total of 200 patients were referred to the department of psychiatry from different out patient departments during a period of six months. Each of them underwent a detailed psychiatric evaluation.Results: The mean age of the patients evaluated was 36.03 years; most of them were females (66.5%), married (67%), educated up to class seven (28%) and housewives (32.5%) living in a nuclear family (62.5%) coming from a middle income socio-economic status (75%). More than half (52%) referrals were from Medical ward coming with the chief complaint of headache (18.5%) followed by disturbance in sleep pattern (17%) and pain in more than three sites (17%). The most common psychiatric diagnosis was depression (49%) followed by anxiety (35.5%). A majority of the patients (55%) perceived their illness to be neurological and had received alternative treatment from a faith healer (26%) before being referred to the psychiatric out patient department.Conclusion: Psychiatric consultation was sought mostly by medical out patient department that had maximum number of patients. The commonest diagnosis seen in the referred out-patients was depression and anxiety disorder. Patients mostly presented with vague somatic complaints such as headache, disturbance in sleep pattern and pain over morethan three sites of the body.